Mephentermine abuse of prescription drugs in gym - Bhardwaj, Ankit; Sharma, Sangeeta; Prakash, Om (International Journal of Basic & Clinical Pharmacology, 2020)
A case report of 32 years old male presented to the drug addiction OPD and treatment center for the withdrawal symptoms of mephentermine. Mephentermine a synthetic derivative of amphetamines with cardiac stimulatory action is been misused for boast of endurance in bodybuilders. Abuse of mephentermine result in psychosis, cardiovascular disorder and development of tolerance and dependence over time. Given its potential of causing harm, the abuse and dependence liability of mephentermine needs to be highlighted to gym instructors and general public.